Analisis Kebutuhan Modul Ajar Matematika untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SMK Kelas X - Fajria Ahmad Difinubun; Makmuri Makmuri; Hidajat Flavia Aurelia (Griya Journal of Mathematics Education and Application, 2022)
The independent learning curriculum requires effective and innovative teaching materials. One of them is a module. This research aim to (1) analyze the need for mathematics textbooks that can improve students' problem-solving abilities according to the Project Based Learning (PjBL) model; (2) identify learning problems faced by students and analyze the suitability of textbooks with the syllabus. This research is descriptive qualitative. The research subjects were mathematics teachers and tenth-grade students of vocational high school. Data regarding learning resources were collected by interviewing mathematics teachers. Data regarding students' problem-solving abilities were collected by observing grade 10th students. Data analysis using data reduction, data presentation, and conclusions. The result shows that: (1) the textbooks used are not in accordance with core competencies, basic competencies, competency achievement indicators, and the questions that are considered difficult by students; (2) there is no learning model applied in textbooks. So that textbooks are needed in the form of modules that can improve students problem solving with the PjBL model; teachers and students stated that they needed textbooks in the form of math modules that could be understood, and motivated in learning, there were many models of real questions so that students agreed and supported the creation and development of math modules to improve problem-solving abilities.